Formulation, In-vitro Evaluation, and Animal Study of Levofloxacin/Tinidazole loaded pH-dependent In-Situ Gel for Ophthalmic Drug Delivery - S Taghi, Hassanien; G Jabar, Esraa; Q Almajidi, Yasir (The Iraqi Journal of Veterinary Medicine, 2024)
Conventional ocular drug delivery forms (eye drops, eye ointments, and eye gels) possess poor bioavailability, less retention, and rapid precorneal discharge. In veterinary medicine, treating eye infections in animals like rabbits, dogs, and cats poses similar challenges. An in-situ gel drug delivery system (ISG-DDS) provides sustained action with a low formulation cost, which can be advantageous for veterinary applications. This study developed and characterised a pH-responsive ophthalmic ISG of levofloxacin and tinidazole with the potential to be used in both human and veterinary medicine. Carboxypol 980 (CBL-980) was used to make the ISG gel, and hydroxypropyl cellulose (HPC) changed the viscosity. Nine formulas of ISG were prepared. To find out about the drug content, clarity, gelling time, pH, viscosity, and stability of the product we got, we did a release study, as well as a DSC and FTIR visual evaluation. Albino rabbits (Oryctolagus cuniculus) were utilized to check for safety and ocular irritation. In Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC), there was no significant interaction between the drug and the additives. This showed that the drug changed into an amorphous form. The results show that ISG was translucent, with a pH ranging from 5.4 ± 0.22 to 7.8 ± 0.26. The ISG formulas 1, 2, and 3 required 39, 36, and 34 minutes, respectively, for gelling and showed approximately 4-5 times more viscosity than all batches. The optimum formula (formula 1) showed the highest drug content, prolonged drug release up to 6 h, stability for 3 months, and safety to use for animals (no indication of inflammation). Tests done in the lab and on animals show that making a pH-dependent ISG that is loaded with Levofloxacin/Tinidazole and used to deliver drugs to the eye has a lot of potential. The in-vitro trials demonstrated a gradual release of the drug over time, a crucial factor in maintaining its presence on the eye’s surface for an extended duration. This is critical for effectively treating eye infections. Animal studies further corroborated the findings, demonstrating their safety. Nevertheless, additional clinical trials are necessary to confirm these findings and evaluate the effectiveness of ISG in real-life situations‎‎‎.